A case of anomalous origin of the left coronary artery from the pulmonary artery presenting with sudden cardiac arrest due to coronary artery steal generated by excessive exercise. Issue 5 (November 2016) - Imamura, Takaaki; Kondo, Hidekazu; Ishii, Yumi; Haraguchi, Miho; Kobukata, Mami; Otsubo, Toyokazu; Saito, Shotaro; Akioka, Hidefumi; Shinohara, Tetsuji; Yufu, Kunio; Takahashi, Naohiko
Abstract: This case report describes a 43-year-old man who temporarily survived cardiac arrest that was prospectively related to ventricular fibrillation due to the anomalous origin of the left coronary artery from the pulmonary artery (ALCAPA). Prior to admission to our hospital, he was asymptomatic for ALCAPA syndrome. Emergent coronary angiography revealed that the dilated right coronary artery was connected with extensive collateral vessels to the left coronary artery. The origin of the latter was in the pulmonary artery. Moreover, coronary steal phenomenon was identified by examining the pulmonary arterial blood oxygen saturation. The patient later died of acute decompensated acidosis. <Learning objective: It is common that oxygen saturation exams may be normal or show a slight increase within the pulmonary artery in this anomaly. However, moderate to severe left to right shunt was remarkably detected in this patient, which may have contributed to acute ischemia in addition to inadequate collateral flow.>